IMPLEMENTATION OF MAQASHID SHARIA IN CONTROLLING THE GROWTH OF THE COVID-19 VIRUS - Uyuni, Badrah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2021)
Abstract In English: The spread of covid-19 in Indonesia coincides with the arrival of Ramadan. In fact, apart from fasting, there are also many other religious rituals, both express and implied in Islamic teachings, which have the value of friendship. The government also issued various regulations which in fact prohibit and limit these religious activities. In fact, the MUI also supported it by issuing a fatwa. By using an interpretive subjective approach and qualitative descriptive methods, this study analyzes data in the form of normative phenomena, social values, and the use of the maqasidsyari'ah method. Conclusions obtained, Fatwa MUI is one of the sources of law and guidance for Muslims in conducting religious activities in the midst of the covid-19 pandemic; Fatwa MUI related to the prohibition and restriction of religious activities in congregation in accordance with some concepts of maqasidsyari'ah.